Allometric Relationships for Biomass and Carbon Estimation of Neem (Azadirachta indica A. Juss) Plantations in Dryland of Hyderabad, Telangana - mohamed, M. B. Noor; Rao, G. Rajeshwar; A, Keerthika; Gupta, Dipak Kumar; Shukla, A. K. (International Journal of Bio-resource and Stress Management, 2018)
The present study was conducted in Central Research Institute for Dryland Agriculture (CRIDA), Hyderabad to develop the allometric equations for predicting the total biomass and carbon of Azadirachta indica in three different basal diameter classes (0-10 cm, 10-20 cm and 20-30 cm). The growth variables viz., tree height, basal diameter, DBH, crown height and crown width are maximum for neem under higher diameter class, whereas minimum under lower diameter class. The average total biomass of neem tree was recorded as 122.3 kg/tree and 338.8 t/ha in all three diameter classes. The allometric relationship between the variables in Azadirachta indica was highly significant with positive and high correlation. The highest and significant linear relationship was observed in tree height (0.992) followed by crown height (0.963) with above ground biomass. With below ground biomass, a strong and highly significant relationship was observed in tree height (0.988) followed by crown height (0.974) and DBH (0.967). The above ground variables (tree height, basal diameter, DBH, crown height and crown width) had highly significant linear relationship with predicted variable of total biomass. The highest and strongest coefficient observed between total carbon and tree height (0.991) followed by crown height (0.968) and DBH (0.957). And also, the significant relationship was found between the dependent variable (total carbon) and other independent variables viz., basal diameter (0.821), and crown width (0.910). Therefore, the result of this study may be useful to predict the amount of total carbon and biomass stored in Azadirachta indica plantation on area basis.